Superficial Palmar Arch Aneurysm after Carpal Tunnel Decompression, a Rare Complication: A Case Report - S. Gull; R. A. J. Spence; W. Loan (Case Reports in Medicine)
False aneurysms of the palmar arteries are rare. They are usually associated with traumatic injuries to the hand vasculature. We present a case of superficial palmar arch aneurysm (SPAA), complicating carpal tunnel decompression which presented as a pulsatile mass at the site of previous surgery. Initial diagnosis was made on clinical examination and confirmed on doppler ultrasound (US) and computed tomographic angiography (CTA). The feeding vessel of the aneurysm was subsequently occluded using coil embolization.